The SAGES manual on the fundamental use of surgical energy (FUSE) - Fuchshuber, Pascal; Jones, Daniel B.; Feldman, Liane (Springer US, 2012)
The SAGES Manual on the Fundamental Use of Surgical Energy (FUSE) emphasizes good communication and promotes best practice for the use of electrosurgical, ultrasonic, and microwave energy sources in the operating theatre. This manual describes the basic technology of energy sources in the operating room and demonstrates the correct use and indications of energy sources in clinical practice. It also addresses the potential complications, hazards, and errors in the use of surgical energy sources and evaluates the potential interactions of energy sources with other medical devices. Any healthcare professional who has ever picked up an energy device in the OR such as a "Bovie" , Ultrasonic or bipolar instrument will better understand how it works, when to apply it, and what are the possible hazards and errors in its use. The SAGES Manual on the Fundamental Use of Surgical Energy (FUSE) is the first volume of its kind to provide such guidance and will be of great value to surgeons, anesthesiologists, nurses, endoscopists, and allied health care professionals who use these devices.